Description of Ornithodoros montensis n. sp. (Acari, Ixodida: Argasidae), a parasite of the toad Rhinella arenarum (Amphibia, Anura: Bufonidae) in the Monte Desert of Argentina - Venzal, José Manuel (2019)
A new tick species of the genus Ornithodoros (Acari: Argasidae) was described from larvae collected on the toad Rhinella arenarum in a locality from Argentina belonging to the Monte Biogeographic Province. Ornithodoros montensis n. sp. was described based on morphological traits and sequences of the mitochondrial 16S rRNA gene. The diagnostic characters for this species are a combination of idiosoma oval, dorsal plate pyriform with posterior margin slightly concave, dorsal surface with 17 pairs of setae (7 anterolateral, 4 to 5 central and 5 to 6 posterolateral), ventral surface with 6 pairs of setae and 1 pair on anal valves, three pairs of sternal setae, postcoxal setae absent, and hypostome pointed apically with dental formula 3/3 in the anterior half and 2/2 posteriorly almost to base. Phylogenetic analysis of 16S rDNA sequences and a principal component analysis based on morphometric characters provided additional support to the description of O. montensis as an independent lineage within the genus Ornithodoros. Larvae of O. montensis are phylogenetically closely related to O. puertoricensis, O. rioplatensis, O. talaje s.s., O. guaporensis, O. hasei and O. atacamensis, all of them belonging to the “O. talaje group”.